Factors affecting presence and diet of red foxes and birds of prey. A large scale study in Finnmark - Anda, Jon Kristian (UiT Norges arktiske universitet, 2015)
In absence of top predators, the red fox population reaches a higher number of individuals. The increased presence of red fox, as it invades alpine and tundra ecosystems, might have severe and negative consequences on the ecosystem as a whole. In Finnmark, Northern Norway, immense levels of large herbivores due to reindeer herding roam the tundra. The high numbers of reindeer provide resources (as carcasses) for scavenging species, a subsidy essential for the survival of the non-endemic predatory species during the low phase of the small rodent population cycle. This large-scale study in 2011, during a small rodent peak year, covers the three peninsulas located in the middle and eastern regions in Finnmark; Porsager, Sværholt and Nordkinn. In this study I map the diet of red fox and birds of prey, and investigate the importance the different factors have on distribution and diet. Expectedly, I discovered that red fox and raptor diets consisted largely of small rodents. Furthermore, it seems that reindeer are not a very important food resource for red fox, and even less important for raptors. This agrees with the fact that no relationship was found abundance of reindeer and abundance of red fox and raptors. Further studies of mesopredator diet should also be conducted during the low phase of the small rodent cycle.